2011
DOI: 10.1167/11.3.23
|View full text |Cite
|
Sign up to set email alerts
|

Color selection, color capture, and afterimage filling-in

Abstract: R. van Lier, M. Vergeer, and S. Anstis (2009) reported an afterimage that produced different percepts from an inducing stimulus depending on the shape of a subsequent contour. G. Francis (2010) explained this phenomenon with a model where the contour forms a boundary that traps the afterimage color as it spreads across a surface. We conducted a series of additional model simulations and experiments to test the explanation. We first tested the hypothesis that the contour traps the afterimage color by adding add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
5
18
2
Order By: Relevance
“…Initially, the results from the model were consistent with the idea that boundaries block color spreading. In a second study however, some predictions of the model did not entirely match their experimental data (Kim and Francis, 2011). Particularly, in one instance they used similar star-like stimuli (see Figure 1) as used in van Lier et al (2009), but varied the size of the test outline.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Initially, the results from the model were consistent with the idea that boundaries block color spreading. In a second study however, some predictions of the model did not entirely match their experimental data (Kim and Francis, 2011). Particularly, in one instance they used similar star-like stimuli (see Figure 1) as used in van Lier et al (2009), but varied the size of the test outline.…”
Section: Discussionmentioning
confidence: 97%
“…An alternative interpretation is that the alignment of a test contour with the edges of the inducing colored region is important for filling-in to occur, because of repeated activation of orientation selective neurons that are also coding for color (Friedman et al, 2003). Kim and Francis (2011) additionally found that when the test contour was larger as compared to matching contours, the probability of perceiving filling-in of an unexpected color became higher, possibly due to the fact that larger test contours included afterimages from two complementary colors. However, when the test contour was smaller than the inducing colored region, the probability of perceiving no color filling-in became higher.…”
Section: Discussionmentioning
confidence: 99%
“…We should distinguish between the neural site of the afterimages themselves, which are probably in the retina, and of the spatial averaging which happens much later, after the point where motion segregates different regions, namely in or after the cortical area MT. Francis (2009Francis ( , 2010 has suggested that Van Lier et al 's (2009) afterimage filling-in phenomena, although new, can be modeled by earlier ideas (presented in Francis & Ericson, 2004;Francis & Schoonveld, 2005) and by Francis' new simulations of the existing boundary contour system/feature contour system model of visual perception (Grossberg, 2003;Grossberg & Mingolla, 1985a, 1985b, although Kim and Francis (2011) have recently shown that the model cannot explain all phenomena related to the afterimage filling-in effect. Feitosa-Santana, D'Antona, and Shevell (2011) have recently found, as we have, that illusory contours can bound the reach of color fillingin, and Hamburger, Prior, Sarris, and Spillmann (2006) and Hamburger, Geremek, and Spillmann (2012) have studied filling-in of real colors and afterimage colors respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These two latter papers also propose that color spreads spatially in a process akin to physical diffusion, until it encounters a luminance contour. The experiments of Kim and Francis ( 2011 ) also showed that their model could not fully account for the spreading of afterimage colors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the superimposed luminance contours modulated the perceived colors: the Gainsborough greyscale made the torso look blue, while the Ingres greyscale made the same torso look pink. With regard to the filling-in of afterimages, Francis ( 2010 ) and Kim and Francis ( 2011 ) explained such contour dependent filling-in effects with a model in which the contour forms a boundary that traps afterimage colors, and presumably real colors, as they spread across a surface. This model in turn draws upon the earlier theories of Grossberg and Mingolla ( 1985 ) and Grossberg ( 2002 ).…”
Section: Introductionmentioning
confidence: 99%